Policy instrument terms in patriotic health campaign documents issued by Chinese national government agencies from 1952 to 2023: a quantitative textual analysis - Yuanyuan LA; He ZHU; Qiqi WANG; Hongyan YAO; Xiaoyun LIANG (Zhongguo gonggong weisheng)
ObjectiveTo analyze the historical development and policy structure of China′s Patriotic Health Campaign policy, in order to provide theoretical, methodological and empirical references for the optimization of relevant policies. MethodsWe collected documents relevant to the Patriotic Health Campaign issued by Chinese national government agencies from 1952 to 2023 from relevant government portals, such as the State Council and the National Health Commission, as well as from Peking University′s Fabao and Legal Star databases. From the perspective of policy instruments, we established a three-dimensional analytical framework by organically combining policy instruments and policy objectives with the policy change process. Content analysis was used to systematically analyze policy goal setting and policy instrument selection at different stages. ResultsA total of 79 policy documents were included in this study. From the perspective of policy instruments, command and control instruments were most frequently used (54.82%) and were the main tools to achieve policy objectives in the process of policy development. Capacity building instruments (23.57%) and information and persuasion instruments (16.28%), as commonly used policy instruments, played an important role in achieving policy objectives. Incentive instruments (3.39%) and systems change instruments (1.95%) were used less frequently. In terms of policy objectives, population health (40.34%) and regional health (50.43%) accounted for a relatively high proportion, while social-ecological system health accounted for a relatively low proportion (9.23%). ConclusionsFrom the perspective of policy instruments, China′s Patriotic Health Campaign-related policies are dominated by command and control instruments, with a lack of use of incentive and system change instruments. In terms of policy objectives, more attention has been paid to population health and regional health objectives, and the preference for policy instrument selection varies with different policy objectives. With the development of policy stages, policy instruments have become increasingly rich and diverse, but their internal distribution is still uneven.